Estudio del plancton en el estuario del río Chaguana - Correa Maldonado, Hernando Edison (2014)
Knowledge of the presence of plankton in nature is critical , because organisms are abundant and have a strong action on the environment and partly involves understanding the onset of successive cycles and energy levels are going to depend on where higher organisms for their survival . This research was based on the study of plankton in the estuary of the river Chaguana Tendales parish in Canton Guabo El Oro province for which we propose the following objective: 1. Qualitatively and quantitatively identify plankton species present in the estuary of the river Chaguana. The study it conducted in 4 areas (A, B , C, D ) of the estuary of the river Chaguana collection is the performed horizontally and applying descriptive statistics in the measurement of phytoplankton if there was supremacy of genera Skeletonema with 48 % of total samples , species of the genera Skeletonema , Coscinodiscus and Nitzschia were the most prevalent in the qualitative analysis. And as a result in the case of homogeneity in the results Zooplankton having presence of organisms such as paramecia , microcrustaceans (copepods ) , insect larvae , veliger and engraulidae Tuberculosa Anadara ( fish eggs ).